Optimizing Technical Training for Wheelchair-User Billiard Players through Modified Equipment Implementation - Viktoriia Nagorna; Artur Mytko; Olha Borysova; Liubov Zhyhailova; Silvio R. Lorenzetti (MDPI AG, 2024)
This study aims to enhance the effectiveness of the preparation process and the performance of wheelchair users in international billiard competitions through modified equipment. The research methods include analysis and synthesis of the scientific and methodological literature, sociological research methods (questionnaires), expert assessment methods, pedagogical research methods (observation, testing, experimentation), and methods of mathematical statistics. The results of our study are significant: Implementing our developed training program for billiards players with musculoskeletal disorders, utilizing the modified equipment (special mechanical bridge and straps for cue fixation during shots) we created in a pedagogical experiment, demonstrated a probable improvement of 36% in the technical and tactical preparedness of the athletes compared to previous years. This led to a 33% increase in players from the Ukrainian team's competition performance at the national and European Pool Championships (wheelchair division). In conclusion, implementing our developed training program, accompanied by specialized auxiliary equipment, demonstrated promising results in a pedagogical experiment. These findings underscore the potential of the modified equipment and tailored training programs to optimize sports training for individuals with musculoskeletal impairments in adaptive billiards, contributing to the continued humanization of the sport and offering an effective preparation process for the athletes.